A monolithic gallium nitride‐based two‐phase synchronous buck converter with high operating frequency. Issue 7 (29th March 2023) - Lai, Longkun; Jiang, Xin; Li, Chenhao; Luo, Weijun
Abstract: The need for a high‐frequency and high‐efficiency gallium nitride (GaN)‐based buck converter that can be controlled directly by a low swing pulse width‐modulated (PWM) signal, without the need for additional buffers or preamplifiers, poses a significant challenge in the field of power conversion and dynamically power supply applications. To solve this problem, this letter presents a monolithic two‐phase synchronous buck converter, fabricated using a 0.25‐um GaN‐on‐Si process, integrated both the drivers and power stage transistors, without requiring additional buffers or preamplifiers. So, the proposed converter can be directly controlled by a PWM signal with a swing of only 1 V (−0.5 to 0.5 V). At a 100‐MHz switching frequency, the converter achieves a maximum output power of 12 W with a power stage efficiency of 82%. The converter includes two identical half‐bridge Monolithic Microwave Integrated Circuit (MMICs), and with the frequency multiplication property of multi‐phase topology, the equivalent switching frequency can reach 200 MHz in the open‐loop operating mode. The experimental results show that the converter can track a 40‐MHz bandwidth envelope signal (256 QAM, 6 dB PAPR) with 80.1% efficiency. Abstract : The need for a high‐frequency and high‐efficiency GaN‐based buck converter that can be controlled directly by a low swing PWM signal, without the need for additional buffers or preamplifiers, poses a significant challenge in the field of power conversion and dynamically power supply applications. To solve this problem, this letter presents a monolithic two‐phase synchronous buck converter, fabricated using a 0.25um GaN‐on‐Si process, integrated both the drivers and power stage transistors, without requiring additional buffers or preamplifiers. So, the proposed converter can be directly controlled by a PWM (Pulse Width Modulated) signal with a swing of only 1V (‐0.5V‐0.5V).